Ultrasmall MoC nanoparticles embedded in 3D frameworks of nitrogen-doped porous carbon as anode materials for efficient lithium storage with pseudocapacitance - Chen, Xiudong; Lv, Li-Ping; Sun, Weiwei; Hu, Yiyang; Tao, Xuechun; Wang, Yong (Journal of materials chemistry. A, Materials for energy and sustainability, 2018)
Transition metal carbides are promising anode candidates for lithium ion batteries, however, their potential accomplishment still requires a rational structural design to improve their low reversible capacities, especially at high current densities and during long-term cycling. This work designs ultrasmall MoC nanoparticles with a diameter of 2–3 nm that are anchored in a three-dimensional (3D) network of nitrogen-doped porous carbon (denoted as MoC–N–C). The MoC–N–C can not only shorten the ion diffusion pathway, leading to fast transport of Li + , but also accommodate the volume expansion and adhesion of MoC nanoparticles during long-term cycling. Consequently, it displays large charge reversible capacities of 1246 mA h g −1 (300 cycles, 100 mA g −1 ), 813 mA h g −1 (500 cycles, 1 A g −1 ) and 675 mA h g −1 (500 cycles, 2 A g −1 ), for lithium ion batteries. In addition to mesoporous properties, large surface area, high ion/electron conductivity, and N-doped characteristics, the excellent lithium storage capability of the MoC–N–C composites, especially at high current densities and during long-term cycling can be mainly ascribed to the significant pseudocapacitance contribution (∼84% at 0.5 mV s −1 ) and synergistic effects between the N-doped 3D conductive network and the in situ generated ultrafine MoC nanoparticles.